Effectiveness of Eye Movement Desensitization and Reprocessing on Quality Of Life in Parents of Children with Cancer - Haji Seyed Javadi, Seyed Alireza; Haji Seyed Javadi, Tahereh (International Clinical Neuroscience Journal, 2017)
Background: Parents of children with cancer face numerous physical, social and economic problems during the care process. Their family, marital, occupational and social life is negatively affected by the process of caring children with cancer which in turn leads to reduced quality of life. The present study examines the effectiveness of eye movement desensitization and reprocessing (EMDR) on quality of life in parents of children with cancer. Methods: This is a quasi-experimental study based on pretest-posttest and follow-up design with a control group. Accordingly, 30 mothers of children with cancer were selected based on targeted sampling method and divided into control and experiment groups. Both groups were pre-tested using the quality of life questionnaire (QoL) (SF=36). Then the experiment group was treated for EMDR for 8 sessions while the control group received no treatment. Following, both groups were post tested and collected data were analyzed using one-way ANOVA on SPSS21. Results: Findings of the study showed that the scores of mothers in experiment group on quality of life increased compared to the control group and maintained at follow-up. The highest increase was on general health, vitality, emotional health, social function while more reduction was on emotional problems of the experiment group (P< 0.01). Conclusion: Regarding the fact that illness of children affects all aspects of parents’ life, and also results of the present study indicating the effectiveness of EMDR on increasing the quality of life in parents of children with cancer, it is suggested to consider psychological training and treatment as the top priority for children with cancer to improve the family function.